2005
DOI: 10.1158/1055-9965.epi-05-0189
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms/Haplotypes in DNA Repair Genes and Smoking: A Bladder Cancer Case-Control Study

Abstract: Bladder cancer is associated with tobacco smoking and occupational exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 39 publications
7
60
0
Order By: Relevance
“…Although polymorphisms of this gene may results in reduced DNA repair capacity, the evidence of direct functional research is limited, and the results of epidemiologic studies in terms of the associations with cancer susceptibility have proved inconsistent Savas et al, 2004;Matullo et al, 2005;Zhang et al, 2005;Ryk et al, 2006;Lee et al, 2007). Our ddata supported this hypothesis, and we found this gene polymorphism would be interact with drinking and AFB1-exposure levels in the process of AFB1-induced ovarian cancer.…”
Section: Discussionsupporting
confidence: 76%
“…Although polymorphisms of this gene may results in reduced DNA repair capacity, the evidence of direct functional research is limited, and the results of epidemiologic studies in terms of the associations with cancer susceptibility have proved inconsistent Savas et al, 2004;Matullo et al, 2005;Zhang et al, 2005;Ryk et al, 2006;Lee et al, 2007). Our ddata supported this hypothesis, and we found this gene polymorphism would be interact with drinking and AFB1-exposure levels in the process of AFB1-induced ovarian cancer.…”
Section: Discussionsupporting
confidence: 76%
“…This was later confirmed by two population-based studies, one conducted in the United States and the other in Poland (36). This variant allele has also been reported to confer a significantly decreased susceptibility to bladder (35), invasive ovarian (21), and upper aerodigestive (37) cancers. However, a few studies have shown no such association with cancer (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 69%
“…For example, some studies have shown the variant allele to be associated with an increased risk for bladder, breast, and lung cancers (30,35,36,40), and these results were in agreement with the results from various functional assays showing that the variant allele was associated with an increased DNA adduct level and compromised capacity to repair X-ray-induced chromosome aberrations (42,43). In contrast, other groups found a lack of association of the T241M SNP with a risk for ovarian, skin, and endometrial cancers (20,21,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The currently available high density of markers in specific chromosomal regions enables us to investigate possible involvement of a number of genes in the development of complex diseases using linkage disequilibrium (LD) to associate markers with disease occurrence at the population level. To our knowledge, few molecular epidemiologic studies have been published on cancer susceptibility associated with XRCC3 haplotypes, [15][16][17][18][19][20][21][22] whose allelic combination may serve as better makers for unknown functional variants than any single nucleotide polymorphism (SNP). Still, to date, and none of studies on XRCC3 haplotypes examined glioma risk.…”
mentioning
confidence: 99%